Emergency/Elective Surgery and Emergency Percutaneous Interventions in Liver Hydatid Cysts and Their Results - Öter, Serdar; Yalçın, Metin (Turkish Journal of Gastroenterology, 2023)
Background: Hydatid cyst may remain asymptomatic for several years or may become complicated. The aim of this study is to evaluate the patients who were operated on for liver hydatid cyst in our clinic and the results of preoperative or postoperative complications. Methods: The data of 836 patients who underwent surgery (n = 750) or Puncture, Aspiration, Injection, and Re-aspiration (n = 86) for hydatid cyst disease in our clinic between January 2006 and January 2021 were evaluated retrospectively. Results: Surgical operation was performed in 750 of the patients and Puncture, Aspiration, Injection, and Re-aspiration procedure was performed in 89 of the patients. In the surgery and Puncture, Aspiration, Injection, and Re-aspiration group, respiratory distress, anaphylaxis, allergic rash, and urticaria were observed in 11 patients (8 in Puncture, Aspiration, Injection, and Re-aspiration group and 3 in open surgery group). All patients recovered with emergency medical interventions. Recurrence was observed after the percutaneous procedure in 11 cases and after surgery in 36 cases. There was no statistically significant difference between the surgical and Puncture, Aspiration, Injection, and Re-aspiration groups in terms of recurrence and cyst infection (P = .253 and P = .547, respectively). The incidence of the development of intrabiliary rupture, allergic reaction, and intraperitoneal rupture was found 135 (16.14%), 12 (1.43%), and 2 (0.23%) in our study, respectively. Conclusions: Intraperitoneal or intrabiliary rupture is a rare but fatal complication of hydatid cyst. The presence of fever, jaundice, abdominal pain, urticaria, and anaphylactic reactions in endemic areas should take the suspicion of hydatid cyst rupture. The timing of surgery is an important factor affecting morbidity and mortality. Detailed exploration of the abdomen in emergency surgery for rupture hydatid cyst is essential for recurrence. Cite this article as: Öter S, Yalçın M. Emergency/elective surgery and emergency percutaneous interventions in liver hydatid cysts and their results. Turk J Gastroenterol. 2023;34(10):1071-1077.